Identification and distribution of a downregulatory signaling alkyloxazole in Streptomyces - Michael Madden; Dan Xue; Mingming Xu; Katherine Holandez-Lopez; Joseph Budiselich; Sarah Tran; Cole Espinosa; Jie Li (Proceedings of the National Academy of Sciences, 2026)
Streptomyces use small molecules to dictate morphological development and secondary metabolism. Most of these signaling compounds are inducers derived from γ-butyrolactone (GBL)-synthesizing enzymes. As such, biosynthetically distinct and downregulatory signaling molecules remain understudied in Streptomyces . Here, we report the identification of alkyloxaozle (AOX, 1 ), a downregulator of sporulation and antibiotic production in Streptomyces . 1 ’s structure features an oxazole head flanked by an alkyl tail synthesized by a nonribosomal peptide synthetase (NRPS) that has not been reported in Streptomyces signaling molecules. Functional studies found that 1 downregulated sporulation and secondary metabolism in several Streptomyces strains. Genome mining identified 45 homologous biosynthetic gene clusters (BGCs) only distributed in Streptomyces , underscoring the importance of AOXs to this productive genus. Altogether, this report presents a downregulatory class of signaling molecules that broadly affect Streptomyces and highlights their importance to the genus.